2017
DOI: 10.1021/acs.jpcb.6b10401
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Protein Intrinsic Normal Mode Weights and Pre-Existing Conformer Populations

Abstract: Intrinsic fluctuations of a protein enable it to sample a large repertoire of conformers including the open and closed forms. These distinct forms of the protein called conformational substates pre-exist together in equilibrium as an ensemble independent from its ligands. The role of ligand might be simply to alter the equilibrium toward the most appropriate form for binding. Normal mode analysis is proved to be useful in identifying the directions of conformational changes between substates. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…All structures were superimposed on the reference wild-type KRas4B-GDP structure at their common α-helix and β-strand residues (rigid parts, 109 residues in total). The distance vector Δ D = [ D 2 , D 3 , D 4 , ..., D 166 ] contains the residue displacements given by Cα displacements between two conformations of the protein (B and A) . Here, the Cα atom coordinates are represented by C i A and C i B , where B is the reference structure coordinates and i is the residue number (from 2 to 166).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All structures were superimposed on the reference wild-type KRas4B-GDP structure at their common α-helix and β-strand residues (rigid parts, 109 residues in total). The distance vector Δ D = [ D 2 , D 3 , D 4 , ..., D 166 ] contains the residue displacements given by Cα displacements between two conformations of the protein (B and A) . Here, the Cα atom coordinates are represented by C i A and C i B , where B is the reference structure coordinates and i is the residue number (from 2 to 166).…”
Section: Methodsmentioning
confidence: 99%
“…between two conformations of the protein (B and A). 43 Here, the Cα atom coordinates are represented by C i A and C i B , where B is the reference structure coordinates and i is the residue number (from 2 to 166).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, Brink et al (2004) were the first to merge discrete classification with the continuous analysis of EM maps through the use of normal modes. Continuous heterogeneity encompasses a whole continuum of conformations adopted by the macromolecule that are accessible by virtue of conformational flexibility, or the so-called intrinsic dynamics (Bahar et al, 2007(Bahar et al, , 2015Ozgur et al, 2017). These motions can be modeled at different scales, from full atomic to coarse-grained, at various levels of resolution, including elastic network models (Bahar et al, 1997;Doruker et al, 2000;Gur et al, 2013;Kurkcuoglu et al, 2016), pseudoatomic representations (Jin et al, 2014;Cazals et al, 2015;, whole domains as rigid entities that move with respect to each other (Tama et al, 2000;Doruker et al, 2002;Ponzoni et al, 2015;Nguyen & Habeck, 2016) or even as a continuous material (Bathe, 2008;Hanson et al, 2015;Sorzano, Martín-Ramos et al, 2016;Solernou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…26 Henzler-Wildman et al showed that apo-ADK can undergo conformational transition in a way that closely resembles the open-to-closed conformational transition. 19 Free ADK can adopt conformations that are not open rather resembles the closed conformation, 27,28 but it is not completely closed, termed "half-open-half-closed" (HOHC) conformation. 7,15,19 The appearance of such state implicates functional relevance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, a conformational selection hypothesis has been proposed to explain the ligand recognition mechanism of ADK. 8,28,31 Many salt bridge interactions at the different domain interfaces of ADK, like the salt bridges LYS136−ASP118 at the LID−CORE interface and LYS57−GLU170 and ASP33−ARG156 at the CORE−NMP and LID−NMP interfaces, respectively, have been shown to exhibit a profound influence on the protein conformational dynamics. 32 However, despite many experimental and theoretical studies, a systematic study of the molecular origin of this conformational dynamics of apo-ADK in terms of its intermediate is yet to be determined.…”
Section: ■ Introductionmentioning
confidence: 99%